The role of tramadol in pain management in Latin America: a report by the Change Pain Latin America Advisory Panel (2017)
Objective: Change Pain Latin America (CPLA) was created to enhance chronic pain understanding and develop pain management improving strategies in this region. During its seventh meeting (August 2016), the main objective was to discuss tramadol’s role in treating pain in Latin America. Furthermore, potential pain management consequences were considered, if tramadol was to become more stringently controlled. Methods: Key topics discussed were: main indications for prescribing tramadol, its pharmacological characteristics, safety and tolerability, effects of restrictions on its availability and use, and consequent impact on pain care quality. Results: The experts agreed that tramadol is used to treat a wide spectrum of non-oncological pain conditions (e.g. post-surgical, musculoskeletal, post-traumatic, neuropathic, fibromyalgia), as well as cancer pain. Its relevance when treating special patient groups (e.g. the elderly) is recognized. The main reasons for tramadol’s high significance as a treatment option are: its broad efficacy, an inconspicuous safety profile and its availability, considering that access to strong analgesics–mainly controlled drugs (classical opioids)–is highly restricted in some countries. The CPLA also agreed that tramadol is well tolerated, without the safety issues associated with long-term nonsteroidal anti-inflammatory drug (NSAID) use, with fewer opioid-like side effects than classical opioids and lower abuse risk. Conclusions: In Latin America, tramadol is a valuable and frequently used medication for treating moderate to severe pain. More stringent regulations would have significant impact on its availability, especially for outpatients. This could cause regression to older and frequently inadequate pain management methods, resulting in unnecessary suffering for many Latin American patients. © 2017 Informa UK Limited, trading as Taylor and Francis Group.